Tetrathiafulvalene – a redox-switchable building block to control motion in mechanically interlocked molecules - Schröder, Hendrik V.; Schalley, Christoph A. (Beilstein Journal of Organic Chemistry, 2018)
With the rise of artificial molecular machines, control of motion on the nanoscale has become a major contemporary research challenge. Tetrathiafulvalenes (TTFs) are one of the most versatile and widely used molecular redox switches to generate and control molecular motion. TTF can easily be implemented as functional unit into molecular and supramolecular structures and can be reversibly oxidized to a stable radical cation or dication. For over 20 years, TTFs have been key building blocks for the construction of redox-switchable mechanically interlocked molecules (MIMs) and their electrochemical operation has been thoroughly investigated. In this review, we provide an introduction into the field of TTF-based MIMs and their applications. A brief historical overview and a selection of important examples from the past until now are given. Furthermore, we will highlight our latest research on TTF-based rotaxanes.
Keywords: artificial molecular machines; mechanically interlocked molecules; molecular switches; supramolecular chemistry; tetrathiafulvalene

(untitled) - Boyer, P. D. (Annu. Rev. Biochem., 1997)

(untitled) - Kinbara, K.; Aida, T. (Chem. Rev., 2005)

(untitled) - Hirokawa, N.; Noda, Y.; Tanaka, Y.; Niwa, S. (Nat. Rev. Mol. Cell Biol., 2009)

(untitled) - Balzani, V.; Credi, A.; Raymo, F. M.; Stoddart, J. F. (Angew. Chem., Int. Ed., 2000)

(untitled) - Coskun, A.; Banaszak, M.; Astumian, R. D.; Stoddart, J. F.; Grzybowski, B. A. (Chem. Soc. Rev., 2012)

(untitled) - Erbas-Cakmak, S.; Leigh, D. A.; McTernan, C. T.; Nussbaumer, A. L. (Chem. Rev., 2015)

(untitled) - Sauvage, J.-P. (Angew. Chem., Int. Ed., 2017)

(untitled) - Stoddart, J. F. (Angew. Chem., Int. Ed., 2017)

(untitled) - Feringa, B. L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Xue, M.; Yang, Y.; Chi, X.; Yan, X.; Huang, F. (Chem. Rev., 2015)

(untitled) - Gil-Ramírez, G.; Leigh, D. A.; Stephens, A. J. (Angew. Chem., Int. Ed., 2015)

(untitled) - Feringa, B. L. (Acc. Chem. Res., 2001)

(untitled) - Kassem, S.; van Leeuwen, T.; Lubbe, A. S.; Wilson, M. R.; Feringa, B. L.; Leigh, D. A. (Chem. Soc. Rev., 2017)

(untitled) - Ballardini, R.; Balzani, V.; Credi, A.; Gandolfi, M. T.; Venturi, M. (Acc. Chem. Res., 2001)

(untitled) - Jørgensen, T.; Hansen, T. K.; Becher, J. (Chem. Soc. Rev., 1994)

(untitled) - Simonsen, K. B.; Becher, J. (Synlett, 1997)

(untitled) - Nielsen, M. B.; Becher, J. (Liebigs Ann./Recl., 1997)

(untitled) - Nielsen, M. B.; Lomholt, C.; Becher, J. (Chem. Soc. Rev., 2000)

(untitled) - Bryce, M. R. (J. Mater. Chem., 2000)

(untitled) - Canevet, D.; Sallé, M.; Zhang, G.; Zhang, D.; Zhu, D. (Chem. Commun., 2009)

(untitled) - Jana, A.; Ishida, M.; Park, J. S.; Bähring, S.; Jeppesen, J. O.; Sessler, J. L. (Chem. Rev., 2017)

(untitled) - Deuchert, K.; Hünig, S. (Angew. Chem., Int. Ed. Engl., 1978)

(untitled) - Wudl, F.; Smith, G. M.; Hufnagel, E. J. (J. Chem. Soc. D, 1970)

(untitled) - Devonport, W.; Blower, M. A.; Bryce, M. R.; Goldenberg, L. M. (J. Org. Chem., 1997)

(untitled) - Scott, B. A.; La Placa, S. J.; Torrance, J. B.; Silverman, B. D.; Welber, B. (J. Am. Chem. Soc., 1977)

(untitled) - Ashton, P. R.; Balzani, V.; Becher, J.; Credi, A.; Fyfe, M. C. T.; Mattersteig, G.; Menzer, S.; Nielsen, M. B.; Raymo, F. M.; Stoddart, J. F.; Venturi, M.; Williams, D. J. (J. Am. Chem. Soc., 1999)

(untitled) - Bryce, M. R. (Adv. Mater., 1999)

(untitled) - Das, A.; Ghosh, S. (Angew. Chem., Int. Ed., 2014)

(untitled) - Griffiths, K. E.; Stoddart, J. F. (Pure Appl. Chem., 2008)

(untitled) - Andréasson, J.; Pischel, U. (Chem. Soc. Rev., 2010)

(untitled) - Spanggaard, H.; Prehn, J.; Nielsen, M. B.; Levillain, E.; Allain, M.; Becher, J. (J. Am. Chem. Soc., 2000)

(untitled) - Khodorkovsky, V.; Shapiro, L.; Krief, P.; Shames, A.; Mabon, G.; Gorgues, A.; Giffard, M. (Chem. Commun., 2001)

(untitled) - Philp, D.; Slawin, A. M. Z.; Spencer, N.; Stoddart, J. F.; Williams, D. J. (J. Chem. Soc., Chem. Commun., 1991)

(untitled) - Torrance, J. B.; Scott, B. A.; Welber, B.; Kaufman, F. B.; Seiden, P. E. (Phys. Rev. B, 1979)

(untitled) - Bozio, R.; Zanon, I.; Girlando, A.; Pecile, C. (J. Chem. Phys., 1979)

(untitled) - Rosokha, S. V.; Kochi, J. K. (J. Am. Chem. Soc., 2007)

(untitled) - Christensen, C. A.; Becher, J.; Christensen, C. A.; Goldenberg, L. M.; Bryce, M. R. (Chem. Commun., 1998)

(untitled) - Hasegawa, M.; Nakamura, K.-i.; Tokunaga, S.; Baba, Y.; Shiba, R.; Shirahata, T.; Mazaki, Y.; Misaki, Y. (Chem. – Eur. J., 2016)

(untitled) - Coffen, D. L. (Tetrahedron Lett., 1970)

(untitled) - Wudl, F.; Wobschall, D.; Hufnagel, E. J. (J. Am. Chem. Soc., 1972)

(untitled) - Ferraris, J.; Cowan, D. O.; Walatka, V.; Perlstein, J. H. (J. Am. Chem. Soc., 1973)

(untitled) - Kistenmacher, T. J.; Phillips, T. E.; Cowan, D. O. (Acta Crystallogr., Sect. B: Struct. Crystallogr. Cryst. Chem., 1974)

(untitled) - Bendikov, M.; Wudl, F.; Perepichka, D. F. (Chem. Rev., 2004)

(untitled) - Wudl, F. (Acc. Chem. Res., 2002)

(untitled) - Jérome, D.; Schulz, H. J. (Adv. Phys., 2006)

(untitled) - Becher, J.; Lau, J.; Leriche, P.; Mørk, P.; Svenstrup, N. (J. Chem. Soc., Chem. Commun., 1994)

(untitled) - Simonsen, K. B.; Svenstrup, N.; Lau, J.; Simonsen, O.; Mørk, P.; Kristensen, G. J.; Becher, J. (Synthesis, 1996)

(untitled) - Svenstrup, N.; Rasmussen, K. M.; Hansen, T. K.; Becher, J. (Synthesis, 1994)

(untitled) - Blanchard, P.; Sallé, M.; Duguay, G.; Jubault, M.; Gorgues, A. (Tetrahedron Lett., 1992)

(untitled) - Challenger, F.; Mason, E. A.; Holdsworth, E. C.; Emmott, R. (J. Chem. Soc., 1953)

(untitled) - Giffard, M.; Frère, P.; Gorgues, A.; Riou, A.; Roncali, J.; Toupet, L. (J. Chem. Soc., Chem. Commun., 1993)

(untitled) - Li, Z.-T.; Stein, P. C.; Svenstrup, N.; Lund, K. H.; Becher, J. (Angew. Chem., Int. Ed. Engl., 1995)

(untitled) - Ballardini, R.; Balzani, V.; Becher, J.; Di Fabio, A.; Gandolfi, M. T.; Mattersteig, G.; Nielsen, M. B.; Raymo, F. M.; Rowan, S. J.; Stoddart, J. F.; White, A. J. P.; Williams, D. J. (J. Org. Chem., 2000)

(untitled) - Sallé, M.; Gorgues, A.; Jubault, M.; Boubekeur, K.; Batail, P. (Tetrahedron, 1992)

(untitled) - Chen, W.; Cava, M. P.; Takassi, M. A.; Metzger, R. M. (J. Am. Chem. Soc., 1988)

(untitled) - Jeppesen, J. O.; Perkins, J.; Becher, J.; Stoddart, J. F. (Org. Lett., 2000)

(untitled) - Jeppesen, J. O.; Becher, J. (Eur. J. Org. Chem., 2003)

(untitled) - Odell, B.; Reddington, M. V.; Slawin, A. M. Z.; Spencer, N.; Stoddart, J. F.; Williams, D. J. (Angew. Chem., Int. Ed. Engl., 1988)

(untitled) - Anelli, P.-L.; Asakawa, M.; Ashton, P. R.; Bissell, R. A.; Clavier, G.; Górski, R.; Kaifer, A. E.; Langford, S. J.; Mattersteig, G.; Menzer, S.; Philp, D.; Slawin, A. M. Z.; et al. (Chem. – Eur. J., 1997)

(untitled) - Brøndsted Nielsen, M.; Hansen, J. G.; Becher, J. (Eur. J. Org. Chem., 1999)

(untitled) - Asakawa, M.; Ashton, P. R.; Balzani, V.; Credi, A.; Mattersteig, G.; Matthews, O. A.; Montalti, M.; Spencer, N.; Stoddart, J. F.; Venturi, M. (Chem. – Eur. J., 1997)

(untitled) - Asakawa, M.; Ashton, P. R.; Balzani, V.; Boyd, S. E.; Credi, A.; Mattersteig, G.; Menzer, S.; Montalti, M.; Raymo, F. M.; Ruffilli, C.; Stoddart, J. F.; Venturi, M.; et al. (Eur. J. Org. Chem., 1999)

(untitled) - Kristensen, R.; Andersen, S. S.; Olsen, G.; Jeppesen, J. O. (J. Org. Chem., 2017)

(untitled) - Nielsen, M. B.; Jeppesen, J. O.; Lau, J.; Lomholt, C.; Damgaard, D.; Jacobsen, J. P.; Becher, J.; Stoddart, J. F. (J. Org. Chem., 2001)

(untitled) - Schmidt, P. M.; Brown, R. S.; Luong, J. H. T. (Chem. Eng. Sci., 1995)

(untitled) - Zhang, Y.-M.; Chen, Y.; Zhuang, R.-J.; Liu, Y. (Supramol. Chem., 2011)

(untitled) - Ziganshina, A. Y.; Ko, Y. H.; Jeon, W. S.; Kim, K. (Chem. Commun., 2004)

(untitled) - Jeon, W. S.; Kim, H.-J.; Lee, C.; Kim, K. (Chem. Commun., 2002)

(untitled) - Yoshizawa, M.; Kumazawa, K.; Fujita, M. (J. Am. Chem. Soc., 2005)

(untitled) - Schröder, H. V.; Wollschläger, J. M.; Schalley, C. A. (Chem. Commun., 2017)

(untitled) - Maksimov, M. O.; Pan, S. J.; James Link, A. (Nat. Prod. Rep., 2012)

(untitled) - Olson, M. A.; Botros, Y. Y.; Stoddart, J. F. (Pure Appl. Chem., 2010)

(untitled) - Ashton, P. R.; Bissell, R. A.; Spencer, N.; Stoddart, J. F.; Tolley, M. S. (Synlett, 1992)

(untitled) - Li, Z.-T.; Stein, P. C.; Becher, J.; Jensen, D.; Mørk, P.; Svenstrup, N. (Chem. – Eur. J., 1996)

(untitled) - Jeppesen, J. O.; Perkins, J.; Becher, J.; Stoddart, J. F. (Angew. Chem., Int. Ed., 2001)

(untitled) - Tseng, H.-R.; Vignon, S. A.; Stoddart, J. F. (Angew. Chem., Int. Ed., 2003)

(untitled) - Deng, W. Q.; Muller, R. P.; Goddard, W. A., III (J. Am. Chem. Soc., 2004)

(untitled) - Jang, Y. H.; Hwang, S.; Kim, Y.-H.; Jang, S. S.; Goddard, W. A., III (J. Am. Chem. Soc., 2004)

(untitled) - Jang, Y. H.; Goddard, W. A., III (J. Phys. Chem. B, 2006)

(untitled) - Zhao, Y.-L.; Dichtel, W. R.; Trabolsi, A.; Saha, S.; Aprahamian, I.; Stoddart, J. F. (J. Am. Chem. Soc., 2008)

(untitled) - Olsen, J.-C.; Fahrenbach, A. C.; Trabolsi, A.; Friedman, D. C.; Dey, S. K.; Gothard, C. M.; Shveyd, A. K.; Gasa, T. B.; Spruell, J. M.; Olson, M. A.; Wang, C.; Jacquot de Rouville, H.-P.; et al. (Org. Biomol. Chem., 2011)

(untitled) - Schröder, H. V.; Sobottka, S.; Nößler, M.; Hupatz, H.; Gaedke, M.; Sarkar, B.; Schalley, C. A. (Chem. Sci., 2017)

(untitled) - Feringa, B. L.; Jager, W. F.; de Lange, B. (Tetrahedron, 1993)

(untitled) - de Silva, A. P.; Dixon, I. M.; Gunaratne, H. Q. N.; Gunnlaugsson, T.; Maxwell, P. R. S.; Rice, T. E. (J. Am. Chem. Soc., 1999)

(untitled) - Avellini, T.; Li, H.; Coskun, A.; Barin, G.; Trabolsi, A.; Basuray, A. N.; Dey, S. K.; Credi, A.; Silvi, S.; Stoddart, J. F.; Venturi, M. (Angew. Chem., Int. Ed., 2012)

(untitled) - Schröder, H. V.; Hupatz, H.; Achazi, A. J.; Sobottka, S.; Sarkar, B.; Paulus, B.; Schalley, C. A. (Chem. – Eur. J., 2017)

(untitled) - Love, J. C.; Estroff, L. A.; Kriebel, J. K.; Nuzzo, R. G.; Whitesides, G. M. (Chem. Rev., 2005)

(untitled) - Balzani, V.; Credi, A.; Venturi, M. (ChemPhysChem, 2008)

(untitled) - Ariga, K.; Mori, T.; Nakanishi, W.; Hill, J. P. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Green, J. E.; Choi, J. W.; Boukai, A.; Bunimovich, Y.; Johnston-Halperin, E.; DeIonno, E.; Luo, Y.; Sheriff, B. A.; Xu, K.; Shin, Y. S.; Tseng, H.-R.; Stoddart, J. F.; et al. (Nature, 2007)

(untitled) - Luo, Y.; Collier, C. P.; Jeppesen, J. O.; Nielsen, K. A.; DeIonno, E.; Ho, G.; Perkins, J.; Tseng, H.-R.; Yamamoto, T.; Stoddart, J. F.; Heath, J. R. (ChemPhysChem, 2002)

(untitled) - Collier, C. P.; Mattersteig, G.; Wong, E. W.; Luo, Y.; Beverly, K.; Sampaio, J.; Raymo, F. M.; Stoddart, J. F.; Heath, J. R. (Science, 2000)

(untitled) - Yu, H.; Luo, Y.; Beverly, K.; Stoddart, J. F.; Tseng, H.-R.; Heath, J. R. (Angew. Chem., Int. Ed., 2003)

(untitled) - Tseng, H.-R.; Wu, D.; Fang, N. X.; Zhang, X.; Stoddart, J. F. (ChemPhysChem, 2004)

(untitled) - Feng, M.; Guo, X.; Lin, X.; He, X.; Ji, W.; Du, S.; Zhang, D.; Zhu, D.; Gao, H. (J. Am. Chem. Soc., 2005)

(untitled) - Huang, T. J.; Brough, B.; Ho, C.-M.; Liu, Y.; Flood, A. H.; Bonvallet, P. A.; Tseng, H.-R.; Stoddart, J. F.; Baller, M.; Magonov, S. (Appl. Phys. Lett., 2004)

(untitled) - Aprahamian, I.; Olsen, J.-C.; Trabolsi, A.; Stoddart, J. F. (Chem. – Eur. J., 2008)

(untitled) - Barin, G.; Coskun, A.; Friedman, D. C.; Olson, M. A.; Colvin, M. T.; Carmielli, R.; Dey, S. K.; Bozdemir, O. A.; Wasielewski, M. R.; Stoddart, J. F. (Chem. – Eur. J., 2011)

(untitled) - Jørgensen, T.; Becher, J.; Chambron, J.-C.; Sauvage, J.-P. (Tetrahedron Lett., 1994)

(untitled) - Dietrich-Buchecker, C. O.; Sauvage, J.-P.; Kintzinger, J. P. (Tetrahedron Lett., 1983)

(untitled) - Nielsen, M. B.; Li, Z.-T.; Becher, J. (J. Mater. Chem., 1997)

(untitled) - Li, Z.-T.; Becher, J. (Chem. Commun., 1996)

(untitled) - Nielsen, M. B.; Thorup, N.; Becher, J. (J. Chem. Soc., Perkin Trans. 1, 1998)

(untitled) - Asakawa, M.; Ashton, P. R.; Balzani, V.; Credi, A.; Hamers, C.; Mattersteig, G.; Montalti, M.; Shipway, A. N.; Spencer, N.; Stoddart, J. F.; Tolley, M. S.; Venturi, M.; et al. (Angew. Chem., Int. Ed., 1998)

(untitled) - Sun, J.; Wu, Y.; Wang, Y.; Liu, Z.; Cheng, C.; Hartlieb, K. J.; Wasielewski, M. R.; Stoddart, J. F. (J. Am. Chem. Soc., 2015)

(untitled) - Rowsell, J. L. C.; Yaghi, O. M. (Microporous Mesoporous Mater., 2004)

(untitled) - Chen, Q.; Sun, J.; Li, P.; Hod, I.; Moghadam, P. Z.; Kean, Z. S.; Snurr, R. Q.; Hupp, J. T.; Farha, O. K.; Stoddart, J. F. (J. Am. Chem. Soc., 2016)

(untitled) - Mondloch, J. E.; Bury, W.; Fairen-Jimenez, D.; Kwon, S.; DeMarco, E. J.; Weston, M. H.; Sarjeant, A. A.; Nguyen, S. T.; Stair, P. C.; Snurr, R. Q.; Farha, O. K.; Hupp, J. T. (J. Am. Chem. Soc., 2013)

(untitled) - McGonigal, P. R.; Deria, P.; Hod, I.; Moghadam, P. Z.; Avestro, A.-J.; Horwitz, N. E.; Gibbs-Hall, I. C.; Blackburn, A. K.; Chen, D.; Botros, Y. Y.; Wasielewski, M. R.; Snurr, R. Q.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2015)

(untitled) - Spruell, J. M.; Coskun, A.; Friedman, D. C.; Forgan, R. S.; Sarjeant, A. A.; Trabolsi, A.; Fahrenbach, A. C.; Barin, G.; Paxton, W. F.; Dey, S. K.; Olson, M. A.; Benítez, D.; et al. (Nat. Chem., 2010)

(untitled) - Frasconi, M.; Kikuchi, T.; Cao, D.; Wu, Y.; Liu, W.-G.; Dyar, S. M.; Barin, G.; Sarjeant, A. A.; Stern, C. L.; Carmieli, R.; Wang, C.; Wasielewski, M. R.; et al. (J. Am. Chem. Soc., 2014)